PENERAPAN MODEL ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SD SWASTA ADVEN TIMBANG DELI - Yentin Naibaho; Darinda Sofia Tajung; Ester J. Simrmata (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to improve students’ learning outcomes on the theme of “Daerah Tempat Tinggalku,” the sub-theme of Bangga terhadap Daerah Tempat Tinggalku, the learning 3 and 4 at grade IV SD Swasta Adven Timbang Deli by using the Role Play model. The subjects in this study were 35 fourth-grade students, and the object of this study was students’ learning outcomes and the role-play model. This type of research was Classroom Action Research. Data collection techniques used were tests and sheets. The results showed an increase in students’ learning outcomes. In the pretest, it was found that the average score was 59.77, and the classical completeness level was 22.8%. In the first cycle, there was an increase after using the Role Play model with an average score of 71.20 and a classical completeness level of 45.71%. And after the actions taken and given posttest in cycle II, the average value increased by 81.00 and the classical completeness level of 88.57%. It was obtained as many as 31 students completed their learning outcomes and four students did not complete. The results obtained show that the Role Play model improved students’ learning outcomes at grade IV SD Swasta Adven Timbang Deli Medan for the 2020/2021 academic year. Based on the research, teachers are advised to use the Role Play model because it is proven to improve students’ learning outcomes.